2009
DOI: 10.1021/pr801061r
|View full text |Cite
|
Sign up to set email alerts
|

Protein Carbonyl Formation in Response to Propiconazole-Induced Oxidative Stress

Abstract: Propiconazole, a widely used fungicide, is hepatotoxic and hepatotumorigenic in mice. Previous genomic analysis of liver tissues from propiconazole-treated mice identified genes and pathways involved in oxidative stress, suggesting that oxidative stress may play a role in propiconazole-induced toxicity. To understand the contribution of oxidative stress on toxicity at the protein level, we developed an integrated approach for the systematic measurement of protein oxidation in the livers from propiconazole-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…The MOA of its carcinogenicity is more likely due to a non-DNA reactive MOA, such as CAR/ PXR nuclear receptor activation, cell proliferation, liver hypertrophy, and/or suppression of apoptosis [Holsapple et al, 2006]. Detection of protein carbonylation following administration of PPZ (2500 ppm in feed) is an indication that oxidative stress can occur following treatment with this high dose [Bruno et al, 2009] and may be a modulating factor. However, to the extent that this occurs, it does not appear to rise to a level that would produce an increase in mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The MOA of its carcinogenicity is more likely due to a non-DNA reactive MOA, such as CAR/ PXR nuclear receptor activation, cell proliferation, liver hypertrophy, and/or suppression of apoptosis [Holsapple et al, 2006]. Detection of protein carbonylation following administration of PPZ (2500 ppm in feed) is an indication that oxidative stress can occur following treatment with this high dose [Bruno et al, 2009] and may be a modulating factor. However, to the extent that this occurs, it does not appear to rise to a level that would produce an increase in mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The US Environmental Protection Agency (EPA) classified propiconazole as a possible human carcinogen [87]; nonetheless, the exact molecular basis for its toxicity remains to be fully elucidated. In their work, Bruno et al [86] found that protein carbonylation, but not thiol modification, increased in response to propiconazole in mouse liver. Carbonylation targets were: key glycolytic enzymes, proteins involved in ATP production, amino acid metabolism, cellular defense and detoxification mechanisms, including redox regulation.…”
Section: Fungicidesmentioning
confidence: 95%
“…Protein carbonyl formation in response to the pesticide propiconazole was investigated in 2008 by Bruno and colleagues [86]. Propiconazole is a systemic fungicide widely used for foliar disease prevention on fruits, vegetables and seeds.…”
Section: Fungicidesmentioning
confidence: 99%
“…In addition to the expression profiling studies, identification of modifications at the gene, protein, and metabolite levels is another important application of OMICS to environmental toxicology and human health research [17,18,19]. It is known that protein carbonylation and phosphorylation are among the major signal transduction pathways in cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…They are currently being studied to determine whether they are also the key to estimate toxicity pathways for environmental pollutants. For example, to understand the contributions of oxidative stress to toxicity, an integrated proteomics approach involving the identification of carbonylated proteins was utilized for the systematic measurement of protein oxidation in the livers of propiconazoletreated mice [17]. This study suggested a mode of propiconazole-induced toxicity in the mouse liver that primarily involves oxidative damage to cellular proteins.…”
Section: Introductionmentioning
confidence: 99%